Sleep Deprivation and Its Effects on Cognitive and Neurophysiological Functions: A Systematic Review: Sleep Deprivation and Its Effects on Cognitive and Neurophysiological Functions - Mehwish, Romana; Riaz, Amna; Ajmal, Amna; Hameed, Shahid; Baig, Imran Mehboob; Samad, Abdul (Pakistan Journal of Health Sciences, 2026)
Sleep deprivation is common among students, healthcare workers, and shift-based occupations and is associated with impaired cognition and altered brain function. Modern electrophysiological and neuroimaging methods (EEG/ERP and functional neuroimaging) help explain neurophysiological mechanisms underlying sleep-loss-related cognitive impairment. Objectives: To systematically evaluate the effects of sleep deprivation on cognitive outcomes and neurophysiological measures in human participants. Methods: This systematic review followed PRISMA 2020 guidelines. PubMed, Scopus, and the Cochrane Library were searched for studies published from January 2021 to December 2025. Eligible studies were original quantitative human research reporting at least one cognitive outcome (e.g., attention, working memory, executive function, reaction time) and one neurophysiological measure (EEG, ERP, fMRI, fNIRS, or multimodal) using total or partial sleep deprivation. Risk of bias was assessed using RoB 2 and the NIH Quality Assessment Tool. Due to heterogeneity, findings were synthesized narratively. Results: Sixteen studies were included. Sleep deprivation consistently impaired vigilant attention and reaction time (increased PVT lapses and slower responses). Executive control and cognitive flexibility were frequently reduced, whereas working memory effects were task- and load-dependent. Neurophysiological changes included altered EEG activity, modulation of ERP components (P300, N2, CNV), and disrupted connectivity in frontoparietal and default mode networks. Conclusions: Sleep deprivation produces reproducible attention and executive deficits, accompanied by parallel neurophysiological alterations, underscoring the critical role of sleep in performance and safety.